Paths of Salt and Artistic Interactions with Cacela Velha: The Performative Dimension in Two Public Art Projects Sustained by an Integrated View of Place - Pinto, Paula (2016)
This paper addresses the concept of an integrated perspective of place through participatory design in public art, as well as the performative dimension in the development of the artistic projects Paths of Salt and Artistic Interactions with Cacela Velha. It begins with the explanation of the guiding concepts of the research and methodologies, such as place, emphatic and participatory approaches, alluding to the active investigation. To finish with a detailed description of both projects and the analysis of its results.